DEFENDERS OF DIVERSITY? The Legacy of the 1965-66 Massacres for a Muslim Youth organization in Indonesia - Ronal Luken-Bull (ADP Publisher, 2023)
Banser is the paramilitary wing of Ansor, the young men’s organization for Nahdlatul Ulama (Renaissance of the Scholars; NU). NU is the largest Islamic organization in Indonesia, and because Indonesia is so large, the largest in the world. It has been long committed to Indonesia as a non-shariah state as well as multi-religious and multi-ethnic nation. Nahdlatul Ulama’s young men’s organization Ansor, seeks to train non-radical Muslim leaders with a range of expertise and foci. Ansor has a sub-organization called Banser which regularly guards Christian churches, liberal Muslims, and businesses from being targeted by extremists like the Islamic Defenders Front. If the present, or even recent, history of Banser and Ansor is that of protecting religious minorities and pluralism, this has not always been the case. Ansor/Banser was an important auxiliary force in the Revolution (1945-1949) and in the 1965-1966 national bloodletting that left 500,000 alleged communists dead. It is even more telling and interesting if we explore the ways in which the newer socially progressive actions are based on conservative, traditional understandings of Islam and not liberal or progressive religious understandings.